ANTIBACTERIAL ACTIVITY OF Dodoneae viscosa LEAF EXTRACT AGAINST SELECTED ENTERIC BACTERIA (FUDMA JOURNAL OF SCIENCES, 2023)
Dodoneae viscosa is a species of flowering and ornamental plant in Sapindaceae family, Australian in origin and known to be distributed in the tropical, subtropical and temperate regions of the world. The plant is used as a traditional medicine in different countries and its various infusions are used to treat many illnesses including sore throats, ulcers, diarrhea and malaria. This study determined the phytochemical components and also the antimicrobial activities of Dodoneae viscosa leaf extract against Salmonella spp and E. coli obtained from previous isolations in Microbiology laboratory of Federal University Dutse Jigawa state. The leaves were extracted using Soxhlet apparatus for ethanol extract and maceration method for aqueous extract after which the phytochemical components were determined using standard methods while agar well diffusion method was used to determine the antibacterial activity. Results of phytochemical screening showed that bioactive compounds including flavonoid, tannins, phenols and saponins were present in both extract. Growth of the organisms: Salmonella spp and E. coli were inhibited with Minimum Inhibitory Concentration of 50mg/ml and 25mg/ml respectively. The results of ethanolic extract had higher percentage yield of 23.6% compared to the aqueous extract with 16.46%. It further showed that the extract contain some potent phytochemical constituents which are known to be of therapeutic values and its antibacterial activity against the two selected enteric bacteria at 50mg/l and 25mg/l indicated its potency as antimicrobial agent hence, could be useful in the treatment of gastroenteritis in future and exploited in pharmaceutical industries for the production of antimicrobial agent.
Keywords: Antibacterial, Activity, Dodoneae viscosa, Pathogens, Leaf, Extracts, Salmonella